Food Waste Management Model Through The Leadership of Women Entrepreneurs in a Sustainable Development Perspective (Study of Entrepreneurs Women's Culinary in Manado City) - Rosdiana Simbolon; Abdul Hakim; Gatot Ciptadi; Wike Wike (Green Publisher Indonesia, 2024)
The waste production is expected to continue to increase every year in proportion to the increasing population of Manado City. The influential role of women when combined with waste problems ranging from preventing waste generation to processing it is considered capable of realizing the SDGs points mentioned above. The purpose of this study is to analyze the leadership style of female culinary entrepreneurs in Manado City, to analyze waste management regulations, especially culinary waste in Manado City, and to formulate a food waste management model through the leadership of female culinary entrepreneurs in Manado City . The results of the study show that the leadership style of women in some female entrepreneurs is responsible, always directing, thinking with a cool head, fair, always discussing problems faced by employees, wise, firm, trying to give employees motivation and examples (becoming a role model). Progress in waste management is in the form of decentralized waste management, in which waste management is separated for each sub-district, so there are 11 sub-districts. In its management, it still prioritizes the 3R principles (Reduce-Reuse-Recycle). Strategies that can be carried out to make residents participate in waste management are forced waste sorting programs, improving quality or increasing the number of 3R TPSTs with good management, simple composting programs at business locations or household locations and realizing socialization programs to culinary entrepreneurs that in order to be able to run a business, if it violates it, sanctions can be given or its business license revoked.